Effect of quench-induced precipitation on microstructure and mechanical properties of 7085 aluminum alloy. (15th October 2017) - Liu, Shengdan; Li, Qun; Lin, Huaqiang; Sun, Lin; Long, Tao; Ye, Lingying; Deng, Yunlai
Abstract: The effects of quench-induced precipitation on microstructure and mechanical properties of 7085 aluminum alloy were investigated by means of hardness test, tensile test, optical microscopy, conventional and high resolution transmission electron microscopy and scanning transmission electron microscopy. Apart from quench-induced η phase, a plate-like Y phase appears with the decrease of cooling rate from 240 K/s to 3.2 K/s after solution heat treatment. η phase exists primarily in recrystallized grains and has little strengthening effect. Y phase mainly exists in subgrains with a high density of dislocations, it has a high aspect ratio and therefore gives rise to higher hardness and strength for the slowly-cooled specimens after natural aging. After further artificial aging, the aspect ratio of the Y phase decreases and its strengthening effect becomes smaller; moreover, the presence of η and Y phases reduces the quantity of metastable η′ strengthening precipitates and therefore leads to a smaller increment in hardness and strength for the slowly-cooled specimens; consequently, the rapidly-cooled specimens have higher hardness and strength than the slowly-cooled ones. Graphical abstract: Highlights: A plate-like phase with a high aspect ratio precipitates in the slowly-cooled 7085 aluminum alloy after solutionizing. The plate-like phase contributes to higher strength of the slowly-cooled and naturally-aged specimens. The plate-like phase exhibits lower aspect ratios after artificial aging and therefore smaller strengthening effect. The plate-like phase decreases the amount of η′ strengthening phase and therefore reduces the strength of slowly-cooled specimens after artificial aging.